Ischemic Left Ventricular Perforation Covered by a Thrombus in a Patient Presenting with Cerebral Ischemia: Importance of Time-Sensitive Performance and Adequate Interpretation of Bedside Transthoracic Echography. (4th February 2016) - Fischer, A. J.; Lebiedz, P.; Wiaderek, M.; Lichtenberg, M.; Böse, D.; Martens, S.; Breuckmann, F.
Abstract : If myocardial infarction remains silent, only clinical signs of complications may unveil its presence. Life-threatening complications include myocardial rupture, thrombus formation, or arterial embolization. In the presented case, a 76-year-old patient was admitted with left-sided hemiparesis. In duplex sonography, a critical stenosis of the right internal carotid artery was identified and initially but retrospectively incorrectly judged as the potential cause for ischemia. During operative thromboendarterectomy, arterial embolism of the right leg occurred coincidentally, more likely pointing towards a cardioembolic origin. Percutaneous interventions remained unsuccessful and local fibrinolysis was applied. Delayed bedside echocardiography by an experienced cardiologist demonstrated a discontinuity of the normal myocardial texture of the left ventricular apex together with an echodense, partly floating structure merely attached by a thin bridge not completely sealing the myocardial defect, accompanied by pericardial effusion. The patient was immediately transferred to emergency cardiac surgery with extirpation of the thrombus, aortocoronary bypass graft placement, and aneurysmectomy. This didactic case reveals decisive structural shortcomings in patient's admission and triage processes and underlines, if performed timely and correctly, the value of transthoracic echocardiography as a noninvasive and cost-effective tool allowing immediate decision-making, which, in this case, led to the correct but almost fatally delayed diagnosis.